Effects of transfusion and splenectomy on globin chain expression in NTDT HbE/β-thalassaemia - Lim, Wai Feng; George, Elizabeth; Sathar, Jameela; Lai, Kuan Teh; Lai, Mei I. (Universiti Putra Malaysia, 2021)
Introduction: Majority of HbE/β-thalassaemia patients resembles the phenotype of non-transfusion dependent thalassaemia (NTDT). Current management strategies are highly diverse, and the objective of this study is to examine the effects of different treatments on multiple parameters in NTDT HbE/β-thalassaemia to further streamline the management of this disorder. Methods: In this cross-sectional study, we analysed the correlation between different treatment strategies with variable parameters including haematological parameter and globin gene expression. Statistical analyses were carried out using non-parametric tests such as Kruskal-Wallis and Mann-Whitney tests. Results: A total of 29 HbE/β-thalassaemia patients were included in the study. Data showed statistically significant differences were observed in the MCV, MCHC levels, reticulocyte count and log α/β fold change between the groups. Further analysis showed higher log α/β fold change in the transfusion only group compared to the non-treated group. Red blood cell count was found to be lower in transfused and splenectomised group compared to transfusion only. Significantly higher MCV level and reticulocyte count was seen in transfusion and splenectomised group compared to both non-treated and transfusion only groups and higher MCH level in the transfusion and splenectomised group compared to transfusion only group. Conclusion: In general, regardless of single or double combined therapies, HbE/β-thalassaemia showed variable changes in laboratory parameters to the therapies received particularly splenectomy.